2009
DOI: 10.1128/jb.01469-08
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal ApbC/Nbp35 Homologs Function as Iron-Sulfur Cluster Carrier Proteins

Abstract: Iron-sulfur clusters may have been the earliest catalytic cofactors on earth, and most modern organisms use them extensively. Although members of the Archaea produce numerous iron-sulfur proteins, the major cluster assembly proteins found in the Bacteria and Eukarya are not universally conserved in archaea. Free-living archaea do have homologs of the bacterial apbC and eukaryotic NBP35 genes that encode iron-sulfur cluster carrier proteins. This study exploits the genetic system of Salmonella enterica to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 42 publications
(41 reference statements)
1
46
0
Order By: Relevance
“…Interestingly, experimental evidence suggests that the ApbC of Salmonella enterica functions in Fe/S cluster biogenesis pathways (41) and homologues from several archaea functionally complement ApbC mutants of S. enterica (42). In addition, biochemical analyses of bacterial ApbC homologues showed that they bind and transfer Fe/S clusters to a yeast apoprotein in vitro (40).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, experimental evidence suggests that the ApbC of Salmonella enterica functions in Fe/S cluster biogenesis pathways (41) and homologues from several archaea functionally complement ApbC mutants of S. enterica (42). In addition, biochemical analyses of bacterial ApbC homologues showed that they bind and transfer Fe/S clusters to a yeast apoprotein in vitro (40).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, only the sufBC and apbC/nbp35 genes involved in Fe-S biogenesis are conserved across archaea with completely sequenced genomes. Like the bacterial and eukaryotic ApbC/ Nbp35 homologs, the M. maripaludis protein forms Fe-S clusters in vitro and may function as a Fe-S cluster carrier protein in cells (46). The suf system in bacteria is important under iron starvation and oxidative stress conditions, and it is the only Fe-S cluster assembly system in certain bacteria, such as Thermatoga maritima, Mycobacterium tuberculosis, and cyanobacteria (5,47), suggesting that suf can function as the sole Fe-S cluster assembly system in some organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although Cfd1 is found in metazoans, most fungi, and a number of Archaea, many other organisms (e.g. plants) only carry an Nbp35 homolog for cytosolic FeS cluster biogenesis (19,21,23). Although it is possible that in the latter organisms the functions expressed in Cfd1 were acquired in a single Nbp35 polypeptide, it is intriguing to speculate that Cfd1 evolved from Nbp35 to provide unique functions important in those organisms that carry it.…”
Section: Cfd1 Role In Cfd1-nbp35 Scaffold Complexmentioning
confidence: 99%
“…The ability to coordinate FeS cluster and donate cluster to apo target proteins is a conserved feature of members of the ApbC/Nbp35 family. Ind1 in mitochondria of mammals (17), ApbC in bacteria and archaea (18,19), and chloroplast HFC101 (20) and AtNBP35 (21) in plants were each shown to coordinate and transfer reconstituted FeS clusters in vitro. Interestingly, in vitro assembly and transfer of FeS clusters on these P-loop NTPases did not require nucleotide binding or hydrolysis.…”
mentioning
confidence: 99%